Prevalence And Epidemiological Correlates of Hypertension Among Labour Population - Mahmood, S E; Srivastava, Anurag; Shrotriya, V P; Shaifali, Iram; Mishra, Payal (National Journal of Community Medicine, 2011)
The average prevalence of hypertension in India is 25% in urban and 10% in rural inhabitants. Prevalence of hypertension has been found to increase in traditional populations undergoing modernization. There is a strong correlation between changing lifestyle factors and increase in hypertension. The objectives of the study were to find out Prevalence of hypertension and identification of associated risk factors amongst labour population of District Bareilly. The cross sectional field study involved 185 respondents, aged 18 years and above using simple random sampling technique. A study instrument which included behavioral risk factor questionnaire (Tobacco use, alcohol consumption and type of diet) and physical measurements of height, weight, waist circumference, hip circumference and blood pressure was used to collect data. Chi- square test and regression analysis were used to analyze data. The overall prevalence of hypertension was found to be 10.81%. Prevalence of hypertension was significantly higher among individuals, aged 40 years and above, with high body mass index and increased waist hip ratio, (P<.05). There is an increase in cases of hypertension amongst labour population of District Bareilly. Weight reduction may lead to decrease in blood pressure of an individual.